Analisis Kualitas Layanan Digital Nayaka Prana Dalam Penanganan Kekerasan Terhadap Perempuan Dan Anak Di Kota Denpasar - I Putu Adi Permana Putra; Kadek Dwi Sugiantari (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2026)
Denpasar City faces a significant challenge with the fluctuating prevalence of violence against women and children, positioning the region as the epicenter with the highest rates of such incidents in Bali Province. This complexity is further exacerbated by the iceberg phenomenon, driven by the limitations of conventional reporting systems, pervasive social stigma, and survivors' apprehensions regarding identity confidentiality. As a strategic intervention, the Denpasar City Government initiated the Nayaka Prana Service in 2020, an innovative public service governance approach adopting a hybrid model to synergize online and offline ecosystems. This study aims to analyze the quality of this digital service using an e-government approach through a descriptive qualitative method. Data were collected via non-participant observation, document analysis, and in-depth interviews with eight key informants. The analytical framework was constructed based on the E-Government Quality (E-GovQual) model. The findings confirm that the institution has successfully achieved operational reliability through cross-channel consistency, ensuring no disparity in service quality between online and offline reporting mechanisms. Regarding information dissemination, the use of social media has proven to act as an effective psychological catalyst, reducing survivors' procedural uncertainty and organically expanding information reach. The novelty of this research lies in demonstrating that effective e-government services for protecting vulnerable groups are not defined by standalone, techno-centric solutions. Instead, success relies on bureaucratic agility in adopting commodity technologies integrated with humanistic interventions, culminating in a victim-centered hybrid model. This study proves that the inherent limitations of digital systems in addressing psychological trauma must be fundamentally supplemented by profound interpersonal empathy. Consequently, the success of digital transformation within the social protection sector heavily depends on the synergy between IT infrastructure efficiency and cross-sectoral service excellence.